Journal: 100 Years / SCIENTIFIC AMERICAN New York November 24, 1906 / BLASTING OUT A REEF IN NEW YORK HARBOR. - Robert Hopler (International Society of Explosives Engineers, 2007)
Some few years ago, when the cruiser “Brooklyn” was passing through the fairway to the southwest of the Battery, the ship being fully equipped with stores, etc., and therefore at her maximum draft, she grounded quite heavily upon some obstruction, and received injuries which necessitated her docking at the Brooklyn navy yard, where extensive repairs had to be made on her damaged bottom.